Investigation of Atrial Vortices Using a Novel Right Heart Model and Possible Implications for Atrial Thrombus Formation. Issue 1 (December 2017) - Gülan, Utku; Saguner, Ardan; Akdis, Deniz; Gotschy, Alexander; Manka, Robert; Brunckhorst, Corinna; Holzner, Markus; Duru, Firat
Abstract The main aim of this paper is to characterize vortical flow structures in the healthy human right atrium, their impact on wall shear stresses and possible implications for atrial thrombus formation. 3D Particle Tracking Velocimetry is applied to a novel anatomically accurate compliant silicone right heart model to study the phase averaged and fluctuating flow velocity within the right atrium, inferior vena cava and superior vena cava under physiological conditions. We identify the development of two vortex rings in the bulk of the right atrium during the atrial filling phase leading to a rinsing effect at the atrial wall which break down during ventricular filling. We show that the vortex ring formation affects the hemodynamics of the atrial flow by a strong correlation (ρ  = 0.7) between the vortical structures and local wall shear stresses. Low wall shear stress regions are associated with absence of the coherent vortical structures which might be potential risk regions for atrial thrombus formation. We discuss possible implications for atrial thrombus formation in different regions of the right atrium.